Preparation and Characterization of Facilitated Transport Membranes Composed of Chitosan-Styrene and Chitosan-Acrylonitrile Copolymers Modified by Methylimidazolium Based Ionic Liquids for CO2 Separation from CH4 and N2 - Ksenia V. Otvagina; Alla E. Mochalova; Tatyana S. Sazanova; Anton N. Petukhov; Alexandr A. Moskvichev; Andrey V. Vorotyntsev; Carlos A. M. Afonso; Ilya V. Vorotyntsev (Membranes, 2016)
CO2 separation was found to be facilitated by transport membranes based on novel chitosan (CS)–poly(styrene) (PS) and chitosan (CS)–poly(acrylonitrile) (PAN) copolymer matrices doped with methylimidazolium based ionic liquids: [bmim][BF4], [bmim][PF6], and [bmim][Tf2N] (IL). CS plays the role of biodegradable film former and selectivity promoter. Copolymers were prepared implementing the latest achievements in radical copolymerization with chosen monomers, which enabled the achievement of outstanding mechanical strength values for the CS-based membranes (75–104 MPa for CS-PAN and 69–75 MPa for CS-PS). Ionic liquid (IL) doping affected the surface and mechanical properties of the membranes as well as the gas separation properties. The highest CO2 permeability 400 Barrers belongs to CS-b-PS/[bmim][BF4]. The highest selectivity α (CO2/N2) = 15.5 was achieved for CS-b-PAN/[bmim][BF4]. The operational temperature of the membranes is under 220 °C.